Proof of Cotangent Formula cot (α - β)

We will learn step-by-step the proof of cotangent formula cot (α - β).

Prove that, cot (α - β) = cot α cot β + 1/cot β - cot α.

Proof: cot (α - β) = cos(α - β)/sin (α - β)

                        = cos α cos β + sin α sin β/sin α cos β - cos α sin β

                        = cos α cos β/sin α sin β + sin α sin β/sin α sin β/sin α cos β/sin α sin β - cos α sin β/sin α sin β, [dividing numerator and denominator by sin α sin β].

                       = cot α cot β + 1/cot β - cot α                     Proved

Therefore, cot (α - β) = cot α cot β + 1/cot β - cot α.


Solved examples using the proof of cotangent formula cot (α - β):

1. Find the value of cot 15°.

Solution:

   cot 15°

= cot (45° - 30°)

= cot 45° cot 30° + 1/cot 30° - cot 45°

= 1 ∙ √3 + 1/√3 - 1       

= √3 + 1/√3 - 1        

= (√3 + 1)^2/(√3 - 1) (√3 + 1)                             

= 3 + 2√3 + 1/3 – 1

= 4 + 2√3/2

= 2 + √3








11 and 12 Grade Math

From Proof of Proof of Cotangent Formula cot (α - β) to HOME PAGE




Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.